Effect of Mooring System Configuration to Flexible Riser Tension - Eko Budi Djatmiko; Murdjito Murdjito; Kunthi U.D. Prabawani (International Journal of Marine Engineering Innovation and Research, 2023)
Floating Storage and Offloading is a floating structure that functions as hydrocarbon temporary storage from wells before being distributed to tankers and carried to production facilities on shore. The important components used to support FSO operations are mooring systems and risers. The mooring system is used to limit FSO movement due to environmental loads. Riser was carried out hydrocarbons from the well to FSO This study aims to analyze the effect of mooring system configurations on flexible riser tension. These variations consist of spread mooring, conventional buoy mooring (4 buoy), and two other variations combine spread mooring and conventional buoy mooring. This analysis shows that the mooring system with 4 buoys has the largest flexible riser tension that is 248 kN, while spread mooring has the smallest flexible riser tension, 55 kN. FSO with conventional buoy mooring configuration has the largest offset and spread mooring configuration has the smallest offset. The lazy wave type has smaller riser tension than the free hanging type, which is 4 – 58%.